Women, society and change: modern trends & patterns - Fathil, Fauziah (Patridge Singapore, 2018)
Changes in human society are inevitable particularly in the modern era of globalization. Members of the society are consequently affected in one way or another having to cope with different or new ideas, perceptions, expectations and worldviews. Authored by different scholars and writers, the book is a compilation of six chapters each dealing with a specific issue in modern or present society. While some chapters discuss issues related to women and change such as women at work, women empowerment, women representation in the media, women health issues, etc, a few dwell on other contemporary issues such as the issue of LGBT from religious perspectives, and work performance in modern public sector from organizational viewpoint.